Analysing the role of morning briefings in enhancing employee performance in the finance department of Mövenpick Resort & Spa Jimbaran Bali - Ni Kadek Arsi Ardini; Ni Wayan Sumetri; Majid Wajdi; Dr. Muhammad Ahmad Mazher; Yusuf Sarkingobir (Journal of Commerce, Management, and Tourism Studies, 2026)
This study aims to examine the implementation of morning briefings as an internal communication tool that supports operational efficiency and enhances employee performance. The research addresses the implementation process, the role of these briefings in supporting employee performance, and the challenges and solutions associated with their execution. Specifically, the study describes the implementation of morning briefings, analyzes their role in supporting employee performance, and identifies the challenges and solutions within the Finance Department at Movenpick Resort & Spa Jimbaran Bali. A descriptive method with a qualitative approach was employed. Data collection involved observation, interviews, and documentation, with informants selected using a purposive sampling technique. Data analysis proceeded through the stages of collection, reduction, presentation, and conclusion drawing. The results indicate that morning briefings are conducted regularly, in a structured manner, and with open communication; consequently, they play a vital role in improving coordination, information dissemination, work readiness, discipline, accountability, and teamwork among employees. Challenges encountered were addressed by adjusting the timing of the briefings, increasing the participation of all team members, and strengthening team communication.